Creating effective teams : a guide for members and leaders - Wheelan, Susan A; Akerlund, Maria; Jacobsson, Christian (California ; London ; New Delhi : SAGE Publications, 1999)
"Based on the authors' many years of consulting experience with teams in the public and private sectors, Creating Effective Teams: A Guide for Members and Leaders describes why teams are important, how they function, and what makes them successful. The texts covers the four stages of team development -forming, storming, norming, and performing- to help readers effectively navigate these different phases. Separate chapters are devoted to the responsibilities of team leaders and team members. Susan A. Wheelan, Maria Akerlund, and Christian Jacobsson highlight common problems that occur frequently in groups as well as provide practical tips, real-life examples, and questionnaires to help address those problems"--
Revised edition of Creating effective teams, 2016.
Includes bibliographical references.
Keywords: Teams in the workplace